PENGARUH TERPAAN KAMPANYE KPU GOES TO CAMPUS DAN BERITA SANKSI PIDANA MENGAJAK ORANG LAIN GOLPUT TERHADAP INTENSI PERILAKU ANTI GOLPUT - Apriliana, Jennifer; Setyabudi, Djoko; Nugroho, Adi (Interaksi Online, 2024)
General elections in a democratic country are carried out to elect a figure as the leader of the country so that all citizens are obliged to vote well and be able to create maximum leadership formation in a country. But in reality, Indonesia, as a democratic country, still has a few percent of people who are apathetic towards politics by abstaining from abstention. This research uses explanatory quantitative research methods and the Theory of Planned Behavior as a framework. Based on hypothesis testing, exposure to the KPU Goes to Campus campaign and news of criminal sanctions inviting other people to abstain had an effect of 13.4% on anti-abstention behavior intentions and had a significance value of 0.001 < 0.05, therefore it can be concluded that the higher the level of exposure to the KPU Goes to Campus campaign and news of criminal sanctions inviting other people to abstain, the higher the anti-voting behavior intentions that appear in a person